PENGEMBANGAN BAHAN AJAR BERBASISMULTIMEDIA SEJARAH KEBUDAYAAN ISLAM (SKI) - Iwan Aprianto (P3M IAI Nusantara Batang Hari, 2015)
Developers have made observations and preliminary field studies (needs assessment) found that the media are often used in the learning process is the book. Unavailability of multimedia-based teaching materials for learning SKI MTs be the basis of selecting the level of this development. This research aims to develop multimedia based teaching materials on the subjects of History of Islamic Culture. Content and work presented, designed with learning theories of communication, cognitive, Cybernetic and Behavioral Learning Theory that became the starting point of the development of teaching materials that will be used by the students. Research and development uses models Lee and Owen, while the procedures in the study of this development are as follows: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation, and use learning model contextual teaching and Learning (CTL).